Vulnerable consumers, their health and urgent supply of electrical energy in Slovenian legal framework - Tomažič, Luka Martin; Bračič, Suzana; Bratina, Borut (Medicine, Law & Society, 2018)
The question of access to a cost-accessible source of electrical energy during the winter months is one of the pressing concerns of social security even in developed states. We will analyse the complex legal, health and economic issues that are connected with the notion of who a vulnerable consumer is as defined in the Slovenian Energy Code (EZ-1). We will do so by analysing the nature of electrical energy in the Slovenian legal framework and then by evaluating the legal solutions proposed for vulnerable consumers. Consequences for an individual’s health, with a focus during the winter months, will be assessed and a comparative overview of legal solutions will be performed. Lastly, we will argue that the current solution may well be economically untenable and that a revision might be in order. Vprašanje dostopa do stroškovno dostopnega vira električne energije v zimskih mesecih je tudi v razvitih državah eden od nujnih vprašanj socialne varnosti. Analizirali bomo kompleksna pravna, zdravstvena in ekonomska vprašanja, povezana s pojmom, kdo je ranljivi potrošnik glede na opredelitev v slovenskem Energetskem zakonu (EZ-1). Tega se bomo lotili z analizo narave električne energije v slovenskem pravnem okviru in nato z oceno zakonskih rešitev, ki so predlagane za ranljive potrošnike. Ocenili bomo posledice za zdravje posameznika, s poudarkom na zimskih mesecih, in podali primerjalni pregled zakonskih rešitev. Sklepno bomo trdili, da bi bila sedanja rešitev lahko ekonomsko nevzdržna, zato bi bila priporočljiva sprememba zakonodaje.